Successful surgical management of cardiac tamponade following direct intrahepatic portosystemic shunt in a child with Budd-Chiari syndrome: A potentially life-threatening situation - Anand Kumar Mishra; Meenakshi Mandal; Irshad R Mohamed; Sadhna Lal; Harish Bhujade (Wolters Kluwer Medknow Publications, 2023)
Direct intrahepatic portosystemic shunt is a technique of portocaval shunting performed through the percutaneous route in patients with Budd-Chiari syndrome. Stent migration into right-sided heart chambers or perforations causing hemopericardium and cardiac tamponade is rare and underreported. In a child with a coexisting decompensated liver disease, surgical intervention and cardiopulmonary bypass can be challenging. However, surgical management in these life-threatening situations is better than redo interventions.